Creation of a Mini Crusher-Grinder for Small Livestock Farms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The purpose of the study is to substantiate the parameters of a mini crusher-shredder for processing coarse feed stalks in farms. The feasibility of using a mini crusher-shredder for processing coarse feed in the conditions of farms and farms with a small number of animals, which has a rotary-type shredder that combines the operations of grinding and crushing, is justified. The research uses the laws and rules of mathematical statistics, mathematical planning of experiments, and the methods given in existing regulatory documents. Experimental studies were carried out to study the influence of the rotor parameters of the mini crusher-shredder on its quality performance. A compact crusher-shredder has been developed, which has a good visibility of the working bodies, high reliability and quality of work due to zoo technical requirements.